Cartera De Crédito Vencida De La Cooperativa De Ahorro Y Crédito San Antonio Ltda Agencia Babahoyo - Alvarado Torres, Yomira Fernanda (2019)
Currently, the savings and credit cooperative is a financial company that exercises various financial functions for each of its members, strengthening the savings and the economy of the families of the Cantón Los Ríos. Cooperatives are organizations formed by natural or legal persons, who wish to join voluntarily, whose objective is to carry out financial activities, strengthening the savings of each of its members. They must be under the principles established in the corresponding laws. The objective of this case is to determine the incidence generated by overdue portfolios in the San Antonio Babahoyo Savings and Credit Cooperative, determining the causes that generate it. It works with different sectors in which it applies a corresponding analysis to its partners to determine its payment availability. This investigation is framed in the sub-lines of investigation of the career "Management of accounting information" of the Faculty of Administration, Finance and Informatics in the Area of ​​Accounting and Auditing prior to obtaining the title ENGINEERING IN ACCOUNTING AND AUDITING. The internal control that the Cooperativa San Antonio handles, in the departments of credits and collection before authorizing the granting of the credit, considers three primordial guidelines for the generation thereof, such as: Determine the ability to pay, perform the analysis of the situation The borrowers' economic situation, and where the credit is directed, as long as these guidelines are not applied, they will be originating so that the credits are badly granted, thus the increase of the overdue portfolios.